2009
DOI: 10.5897/ajb2009.000-9465
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of PAHs by fungi in contaminated-soil containing cadmium and nickel ions

Abstract: The study investigated the degradation of the polycyclic aromatic hydrocarbons (PAH) benzo(a)anthracene, benzo(a) fluoranthene, benzo(a) pyrene, chrysene and phenanthrene in a soil that was sterilized and inoculated with the nonligninolytic fungi, Fusarium flocciferum and Trichoderma spp. and the ligninolytic fungi, Trametes versicolor and Pleurotus ostreatus in the presence of cadmium (Cd) and nickel (Ni) during a ten week incubation period. The soil pH was initially 5.3 and after amendment increased to 7.0. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The detailed PAHs biodegradation efficiencies in B and BS were respectively: 36.12 and 8.17% for benzo(b,k)fluoranthene; 42.27 and 11.73% for benzo(a)pyrene, and 28.27 and 5.88% for benzo(g,h,i)perylene. This result is rather coincident with the criterion that correlates the increase in recalcitrance of PAHs with the molecular weight and number of aromatic rings, as described previously (Atagana, 2009;Serrano Silva et al, 2009), though such conclusions have been contested by other authors (Tiehm et al, 1997;Rafin et al, 2000;Wu et al, 2008;Hesham et al, 2016;Fayeulle et al, 2019). The efficient removal of benzo(a)pyrene could be explained by the relatively high initial concentration of this PAH, which could generate concentration gradients that enhanced its mass transfer rate toward microorganisms, as described previously by Li et al (2007).…”
Section: Polycyclic Aromatic Hydrocarbonssupporting
confidence: 83%
See 1 more Smart Citation
“…The detailed PAHs biodegradation efficiencies in B and BS were respectively: 36.12 and 8.17% for benzo(b,k)fluoranthene; 42.27 and 11.73% for benzo(a)pyrene, and 28.27 and 5.88% for benzo(g,h,i)perylene. This result is rather coincident with the criterion that correlates the increase in recalcitrance of PAHs with the molecular weight and number of aromatic rings, as described previously (Atagana, 2009;Serrano Silva et al, 2009), though such conclusions have been contested by other authors (Tiehm et al, 1997;Rafin et al, 2000;Wu et al, 2008;Hesham et al, 2016;Fayeulle et al, 2019). The efficient removal of benzo(a)pyrene could be explained by the relatively high initial concentration of this PAH, which could generate concentration gradients that enhanced its mass transfer rate toward microorganisms, as described previously by Li et al (2007).…”
Section: Polycyclic Aromatic Hydrocarbonssupporting
confidence: 83%
“…Chemical analysis showed a total nitrogen and phosphorous content of 300 mg-N kg −1 and 6 mg-P kg −1 , respectively, a moisture of 12% (w/w), and a water holding capacity 34% (w/w). Elemental analysis yielded a molar ratio C(carbon):H(hydrogen):N(nitrogen):S(sulfur) of 13:3:0.2:0.6, which indicated that the C:N ratio was slightly above the recommended values (25:1:1 to 38:1:1), according to Atagana (2009) and Alexander (1999), for the fungal PAHs bioremediation under an optimum water and oxygen content. The comparative elemental analysis of a pristine soil sample taken near the polluted site under study indicated that the carbon content in the later was increased from 2% up to 13% (Supplementary Table 1).…”
Section: Soil Characterizationmentioning
confidence: 82%
“…Nickel is one of the elements necessary for the growth of microorganisms and plays essential roles in various microbial cellular processes when incorporated into nickel-dependent enzymes (acetyl CoA decarbonylase/synthase, urease, methylenediurease, Ni-Fe hydrogenase, carbon monoxide dehydrogenase, methyl coenzyme reductase) [18]. In excessive amounts, it becomes toxic to microorganisms, which in turn leads to inhibition of the bacteria growth and decomposition of organic compounds [19,20]. Four mechanisms of nickel toxicity are distinguished: (a) Ni replaces the essential metal of metalloproteins, (b) Ni binds to catalytic residues of non-metalloenzymes, (c) Ni binds outside the catalytic site of an enzyme to inhibit allosterically, (d) Ni indirectly causes oxidative stress [18,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of other hydrocarbons, the presence of Ni 2+ ions caused: acceleration of the toluene degradation by P1 and P19 strains [33] and inhibition of the crude oil or phenanthrene biodegradation [20,[34][35][36][37]. The bacteria: Pseudomonas aeruginosa CA207Ni, Burkholderia cepacia AL96Co and Corynebacterium kutscheri FL108Hg grew in hydrocarbon media amended with nickel and cobalt (at 5.0 mM) without any changes due to metal toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation